2017
DOI: 10.1093/zoolinnean/zlw031
|View full text |Cite
|
Sign up to set email alerts
|

Low intraspecific genetic divergence and weak niche differentiation despite wide ranges and extensive sympatry in two epigean Niphargus species (Crustacea: Amphipoda)

Abstract: 20The amphipod genus Niphargus comprises hundreds of eyeless and depigmented species with 21 narrow ranges in Western Palaearctic subterranean freshwaters. Two morphologically and 22 ecologically similar species, N. hrabei and N. valachicus, are atypical due to their epigean 23 lifestyle and large ranges. Given their wide and largely sympatric distributions, we explored 24 their potential ecological niche overlap by comparing morphological functional traits, patterns 25 of co-occurrence and habitat selection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…However, ribosomal DNA markers such as intervening spacer sequences (ITSs) are also characterized by small effective population sizes due to their concerted mode of evolution, and their fast mutation rates make them ideal candidate markers for single‐locus species delimitation. Although they remain rare, studies using single diploid sequence markers to delineate species are presently on the rise, either alone (Adjeroud et al., ; Daïnou et al., ) or in conjunction with an organellar marker such as COI (Copilaş‐Ciocianu et al., ; Flot, Dahl, & André, ; Papakostas et al., ). Our take‐home message may therefore be: if you sequence a single marker to delineate species, make it a nuclear one; and if you sequence two markers, include at least one nuclear marker (instead of piling up two mitochondrial or chloroplastic DNA regions, which behave as a single marker because they are linked together on the same molecule).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…However, ribosomal DNA markers such as intervening spacer sequences (ITSs) are also characterized by small effective population sizes due to their concerted mode of evolution, and their fast mutation rates make them ideal candidate markers for single‐locus species delimitation. Although they remain rare, studies using single diploid sequence markers to delineate species are presently on the rise, either alone (Adjeroud et al., ; Daïnou et al., ) or in conjunction with an organellar marker such as COI (Copilaş‐Ciocianu et al., ; Flot, Dahl, & André, ; Papakostas et al., ). Our take‐home message may therefore be: if you sequence a single marker to delineate species, make it a nuclear one; and if you sequence two markers, include at least one nuclear marker (instead of piling up two mitochondrial or chloroplastic DNA regions, which behave as a single marker because they are linked together on the same molecule).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…For example, in different parts of United States, 20%-45% of subterranean species are single-site endemics (Christman, Culver, Madden, & White, 2005;Niemiller & Zigler, 2013), while in France, 38% of aquatic subterranean species have latitudinal linear range extents <3 km (Ferreira, Malard, Dole-Olivier, & Gibert, 2007). In general, aquatic subterranean species with linear range extents above 200 km are an exception (Copilaș-Ciocianu et al, 2017;Eme et al, 2018;Trontelj et al, 2009;Zagmajster et al, 2014). The extremely high proportion of rare species leads to an intuitive hypothesis that they are essential in formation of SRPs.…”
Section: Introductionmentioning
confidence: 99%
“…The first cluster is further split into three subclusters corresponding to 424 lake, lake giant and daddy-longlegs ecomorphs Although most of the surface-water Niphargus species have known populations 455 both in subterranean and surface / ecotonal habitats (Fišer C. et al, 2006;2010b;2014;456 Fišer Ž. et al, 2015), N. hrabei and N. valachicus are probably the most detached from the Therefore, it appears that there were at least two independent colonization events of truly , 2016;Borza et al, 2017;Mauchart et al, 2017). Experimental evidence has shown that niphargids can tolerate hypoxia and other adverse environmental conditions much 495 better than surface-water gammarids (Danielopol et al, 1994;Hervant et al, 1995;Malard 496 and Hervant, 1999;Coppellotti Krupa and Guidolin, 2003;Simčič et al, 2005Simčič et al, , 2006Flot 497 et al, 2014).…”
mentioning
confidence: 99%